(untitled) (Encuentros, 2017)
This article presents an analysis of the processes of permutation that has suffered the music of verbena, in the city of Barranquilla, through a cultural hybridization, which has been based on new processes of technological mediation and cultural appropriation, factors that have influenced widely in major stages of construction of Colombian popular music. The case study was developed from in-depth interviews with members of the group Systema Solar and documentary and literature review. Among the findings are two elements in the background of the process of accumulation of symbolic capital in these new musical African music, Barranquilla, Symbolic Capital, Cultural Capital, Cultural Hybridization, Cosmopolitanism, Mediation Technology, Popular Music, Verbena. expressions: 1) a process of technological mediation, from the incorporacón equipment and new production techniques such as remixing songs, for example, and 2) the apropación of a Caribbean ethos, defined not from a territorial identity but meaningless.